Archaeology and Heritage of the Human Movement into Space
XVIII, 166 p. 29 illus., 15 illus. in color.
Keywords: This volume addresses the creation, documentation, preservation, and study of the archaeology of lunar, planetary, and interstellar exploration. It defines the attributes of common human technological expressions within national and, increasingly, private exploration efforts, and explore the archaeology of both fixed and mobile artifacts in the solar system and the wider galaxy. This book presents the research of the foremost scholars in the field of space archaeology and heritage, a recent discipline of the field of Space Archaeology and Heritage. It provides the emerging archaeological perspective on the history of the human exploration of space. Since humans have been creating a vast archaeological preserve in space and on other celestial bodies. This assemblage of heritage objects and sites attest to the human presence off the Earth and the study of these material remains are best investigated by archaeologists and historic preservationists. As space exploration has reached the half century mark, it is the appropriate time to reflect on the major events and technological development of this particular unique 20th century arena of human history. The authors encapsulate various ways of looking at the archaeology of both fixed and mobile human artifacts in the solar system. As missions continue into space, and as private ventures gear up for public and tourist visits to space and to the Moon and even Mars, it is the appropriate time to address questions about the meaning and significance of this material culture.